Penguatan Keluarga Sebagai Upaya Pengendalian Stunting di Desa Betteng Kecamatan Pamboang Kabupaten Majene Sulawesi Barat - yunus, Evawaty (Journal of Health Education and Literacy, 2021)
Background: Inadequate nutritional intake for a long time due to improper feeding that doesn’t have the proper nutritional needs could cause chronic malnutrition or stunting. Intervention by giving out counseling about Interprofessional Collaboration on family strengthening could increase the public’s awareness on stunting.Objectives:This research objective is to see the impact of interventions (counseling and Focus Group Discussion) on the strengthening the families on the Interprofessional Collaboration program. Methods: This research was conducted using quantitative method with pre-experimental design with one group pre-test and post-test design. Samples were taken on this research using 30 respondents. The instrument used was a questionnaire with questions related to the subject, interviews, and the results of the Focus Group Discussion. Results: Based on the univariate data analysis, we obtained the 36,6% of the age distribution group is the ≥40-59 age group, 53,3% of the respondents’ educational background is university/bachelor degrees, and 46,7% of the respondents are self-employed. Based on the bivariate analysis, we obtained the result on the impact of intervention by counseling on the family strengthening to control stunting with the α value (0,05) > ρ value (0,084). Conclusions: Based on this research we could conclude that there’s a change in the respondent’s knowledge before and after the intervention has been done.